1986
DOI: 10.1111/j.1476-5381.1986.tb10835.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of in vitro anaphylaxis of guinea‐pig isolated tracheal segments by azelastine, inhibitors of arachidonic acid metabolism and selected antiallergic drugs

Abstract: 1 The ability of azelastine to influence antigen-induced contractile responses (Schultz-Dale phenomenon) in isolated tracheal segments of the guinea-pig was investigated and compared with selected antiallergic drugs and inhibitors of arachidonic acid metabolism. 2 Indomethacin produced a significant leftward shift of the antigen concentration-effect curve. 3 The inhibitory activity ofazelastine on anaphylactic responses in guinea-pig trachea was dependent on the duration of exposure (preincubation period). 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…Antiallergic drugs have been demonstrated to in hibit the release of histamine from mast cells and ba sophils [33,34], to block smooth muscle contraction to various spasmogens [35], and to relax airway smooth muscle [15]. We found that azelastine inhibited O3 generation in PMNs from asthmatic patients in a dose-dependent fashion.…”
Section: Discussionmentioning
confidence: 66%
“…Antiallergic drugs have been demonstrated to in hibit the release of histamine from mast cells and ba sophils [33,34], to block smooth muscle contraction to various spasmogens [35], and to relax airway smooth muscle [15]. We found that azelastine inhibited O3 generation in PMNs from asthmatic patients in a dose-dependent fashion.…”
Section: Discussionmentioning
confidence: 66%
“…Such constrictions are caused by many bronchoactive substances released from mast cells [15][16][17]. In the present study, we reported the effects of NZ-107, amlexanox, DSCG and salbutamol on the anti gen-induced contraction of isolated human tracheal mus cle passively sensitized with atopic serum.…”
Section: Discussionmentioning
confidence: 70%
“…Since some investigators have reported that an leukotriene receptor antagonist (FPL-55712) and a lipoxygenase inhibitor (NDGA) inhibited the antigen-induced contrac tion of isolated guinea pig tracheal muscle [16,21,22], lipoxygenase products, especially leukotrienes, are con sidered to play an important role in the antigen-induced contraction of tracheal muscle. Regarding the effects of NZ-107, Yamamoto et al [2] reported that NZ-107 inhib ited the antigen-induced contraction of isolated guinea pig tracheal muscle by inhibiting SRS-A release and its re sponses.…”
Section: Discussionmentioning
confidence: 99%
“…此 外, 苯并吡喃及其衍生物还广泛应用于抗发育不良 [2] 、 抗过敏 [3] 、抗菌、抗癌 [4,5] 、抗过敏性气管炎 [6] 及治疗糖 尿病 [7] 等方面. 氧杂蒽为含有苯并吡喃结构单元的化合 物, 其良好的生物活性(如抗痉挛和调节植物生长等 [8] )…”
unclassified